Career Profile of Home Economics Post Graduates from RLAK Che Karachi - Hakeem, Rubina; Perveen, Madiha; Naseem, Rumaisa; Bano, Naveeda; Ain, Qurat-ul-; Hafeez , Khalida (Nurture, 2010)
In Pakistan home economics was introduced in 1952 and graduates of this field have been entering various vocational fields. However there is a gross misconception among general public and policy makers about its vocational importance. This study was conducted to assess the rate of utilizing home economics education for gainful employment by students of Rana Liaqat Ali Khan Government College Of Home Economics Karachi who completed post graduate education from 1960 to 2006. Sample was recruited through snow ball technique and at least a few person form each year were contacted to get information about gainful employment of the respondent and their classmates. It was revealed that during all decades at least 60% of the postgraduates entered gainful employment. It is hoped that results of this study would help in clarifying misconceptions about home economics and such studies needs to be conducted on a larger scale.